ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA PADA MATERI BARISAN DAN DERET ARITMATIKA - Luti, Atrina; Setiawan, Beni; Delila Pentaugus, Tetrosa (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
The background of this research is students' mistakes in mathematical reasoning on arithmetic sequences and series material in class XI IIS Sma Joseph Khatulistiwa. From the results that have been observed by researchers, one of the causes of student errors in working on the description test questions is the lack of students' mathematical reasoning. The purpose of this study was to analyze students' mathematical reasoning in doing math problems, to explain the barriers to students' mathematical reasoning and to overcome the inhibiting factors of students' mathematical reasoning. This study uses a descriptive method with a qualitative approach. The subjects of this study were 9 students of Joseph Khatulistiwa High School. The instrument used in this study used a description test of 3 questions for high school students in class XI IPS. There are 3 ways to analyze the data, namely by collecting the results of the description test. Collecting data by connecting students' mathematical reasoning test questions. To find out students' errors using arithmetic sequences and series material. The results of this research test will use indicators from mathematical reasoning, namely: (a) draw a conclusion, (b) determine a pattern. From the test results, it was shown that none of the students could answer correctly. By using the Newman error guide indicator, this means that students have not been able to understand a question and have not been able to think logically